Assessment of training needs on crop production for farmers in some selected areas of Bangladesh (Bangladesh Journal of Agricultural Research, 2018)
The study attempts to determine the training needs of the farmers emphasizing nine selected major thematic areas. Under each major component, specific and relevant training needs item were collected and systematically incorporated into an interview schedule and administered in terms of frequency of training imparted. Four districts were purposively selected for the study and a total of eighty farmers were randomly selected from four districts. Primary data were analyzed using descriptive statistics. The study revealed that more male was involved in farming and 45% farmers were middle age category (30-39 years). Majority of the farmers completed primary level of education compared to other categories and family size of more than half (60 %) of the respondents was three. Majority number of respondents (57%) had more than 10 years farming experience. A small number of farmers (8.75%) had owned agricultural land and 45% had land between 0.50- 1 hectare. More than 75% of annual gross income of 57.50% farmers came from agricultural activities. More than half (55%) of the respondents collected information on crop and its varieties by own attempt while about 34% was informed from seed seller or dealer. Farmers in Chattogram district had first priority to get training on integrated pest and diseases management, production of bio control agents and bio pesticides, marketing and transportation. Water management, integrated pest and disease management, vermi-compost production, marketing and transportation ranked first in Khagrachori district. The areas of priority for training in Rajshahi district were production and management technology, processing and value addition, marketing and transportation, integrated pest and disease management, water management and vermi-compost production. Training on integrated pest and disease management, bio-control of pests and diseases, production of bio control agents and bio pesticides, production of off-season vegetables, vermi-compost production, marketing and transportation were most emphasized by the respondents in Rangpur district. Respondents defined identification of adulterated fertilizer, insecticide and pesticide application, disease and insects of mango varieties and fruit bagging system of mango as very good type of training. The study concluded that there is an urgent need to design regular training programs in identified thematic areas to fulfill the knowledge gap among the farmers of Bangladesh.Bangladesh J. Agril. Res. 43(4): 669-690, December 2018